2020
DOI: 10.1136/gutjnl-2020-320777
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between the gut microbiota and monocyte-like macrophages mediates an inflammatory response to promote colitis-associated tumourigenesis

Abstract: ObjectiveMacrophages are among the most abundant cells in the colon tumour microenvironment, and there is a close relationship among monocytes, macrophages and the gut microbiota. Alterations in the gut microbiota are involved in tumour development, but the underlying mechanisms remain unclear. We aim to elucidate the temporal changes in macrophage subsets and functions, and how these dynamics are regulated by microbial cues in the initiation of colitis-associated cancer.DesignA mouse model of colitis-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 52 publications
1
80
0
Order By: Relevance
“…LPS production is also responsible for inducing monocyte-and macrophage-mediated inflammation in the intestine (Wang et al, 2020). Gut macrophages, which reside in the connective tissue underlying the gut epithelium, the lamina propria, are considered key players for the maintenance of intestinal homeostasis and inflammation (Yang et al, 2020). We observed that in ileal tissues, the percentage of macrophages (CD11c + /F4/80 + ) and the cell mass of CD11c-positive monocytes were significantly decreased with both doses of SZ-A compared with the control (Figure 4F).…”
Section: Discussionmentioning
confidence: 99%
“…LPS production is also responsible for inducing monocyte-and macrophage-mediated inflammation in the intestine (Wang et al, 2020). Gut macrophages, which reside in the connective tissue underlying the gut epithelium, the lamina propria, are considered key players for the maintenance of intestinal homeostasis and inflammation (Yang et al, 2020). We observed that in ileal tissues, the percentage of macrophages (CD11c + /F4/80 + ) and the cell mass of CD11c-positive monocytes were significantly decreased with both doses of SZ-A compared with the control (Figure 4F).…”
Section: Discussionmentioning
confidence: 99%
“…The overall importance of TLR4 signaling on acute colitis and CAC development has been intensely studied in murine models using TLR4 -/mice and TLR4 inhibitors, such as TAK-242 or antagonist TLR4 antibodies (15,24,35). Although complete deletion of TLR4 in TLR4 -/mice did not protect from severe DSS-induced inflammation (36), the specific lack of TLR4 signaling on colonic epithelial cells inhibited CAC development, as well as recruitment and activation of Cyclooxygenase (Cox)-2 expressing macrophages in the AOM/ DSS model (14,16).…”
Section: Discussionmentioning
confidence: 99%
“…As macrophages are the immune cells in the lamina propia with the strongest TLR4 expression, we further investigated the impact of TAK-242 and Abx treatment on macrophages. Of note, CAC is associated with a strong infiltration of myeloid cells into the lamina propia (24). Mice suffering from AOM/DSS induced CAC exhibited higher LPMCs counts than ctrl mice.…”
Section: Reduced Tumor Growth After Tak-242 or Antibiotic Treatment Is Associated With Low Frequencies Of Tumor-infiltrating Macrophagesmentioning
confidence: 93%
“…Accumulating data also indicated that the percentage of M2 macrophage is inversely related to increasing the risk for the progression of cancer [46,47]. For CRC patients, increased numbers of M2 macrophage had been found in peripheral blood, tumor-draining lymph node (DLN), and tumor microenvironment [48].…”
Section: Discussionmentioning
confidence: 99%